The Historian as the Bearer of Memory: History and Playfulness - Strobach, Vít (Dějiny – teorie – kritika, 2009)
The historian as a bearer of memory has always laid claim to truth, but has largely failed to admit its dynamic character. That character can be grasped only within history, not outside it. The ‘modern’ historian decided to solve that problem, by trying to sever history’s ties to myth and art. Both, however, remained profoundly incorporated in its telling. The author considers the way to the objectivity of the telling of history to be the acceptance of the rules of the game as a means of dialogue and the return to art or admitting to the creative character of the telling of history. The closeness to truth should therefore be also determined by the criterion of art, which looks beyond the ‘real nature’ of things to their imposed topicality and fullness. And that is revealed only in the multiplicity of subjective testimony and on the boundary of possible interpretation.